Genetics and Genomics of Congenital Heart Disease. Issue 6 (17th March 2017) - Zaidi, Samir; Brueckner, Martina
Abstract : Congenital heart disease is the most common birth defect, and because of major advances in medical and surgical management, there are now more adults living with congenital heart disease (CHD) than children. Until recently, the cause of the majority of CHD was unknown. Advances in genomic technologies have discovered the genetic causes of a significant fraction of CHD, while at the same time pointing to remarkable complexity in CHD genetics. This review will focus on the evidence for genetic causes underlying CHD and discuss data supporting both monogenic and complex genetic mechanisms underlying CHD. The discoveries from CHD genetic studies draw attention to biological pathways that simultaneously open the door to a better understanding of cardiac development and affect clinical care of patients with CHD. Finally, we address clinical genetic evaluation of patients and families affected by CHD.